Can someone remind me which Binomial Expansion formula is used to expand: $\displaystyle \frac{1}{1+x^2} = 1 + (-1)x^2 + \frac{(-1)(-2)}{2!}(x^2)^2 + \frac{(-1)(-2)(-3)}{3!}(x^2)^3+...$ Thanks in advance.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Air Can someone remind me which Binomial Expansion formula is used to expand: $\displaystyle \frac{1}{1+x^2} = 1 + (-1)x^2 + \frac{(-1)(-2)}{2!}(x^2)^2 + \frac{(-1)(-2)(-3)}{3!}(x^2)^3+...$ Thanks in advance. You can do it much easier using the sum of an infinite geometric series formula: $\displaystyle 1 + r + r^2 + \, .... = \frac{1}{1 - r}$ (provided |r| < 1). In your case $\displaystyle r = -x^2$.
If you really want to do it using the (generalized) binomial expansion, do it as $\displaystyle (a+ 1)^n$ with $\displaystyle a= x^2$ and n= -1.
View Tag Cloud